The Problematic Hebrew Verb ‘תשא’ in NAHUM 1:5 - Chia Philip Suciadi (Perichoresis: The Theological Journal of Emanuel University)
The Hebrew word ‘ותשא’ poses difficulties for ancient translations, Hebrew lexicons (BDB and HALOT), and the Old Testament scholars, as it can be interpreted as either ‘נשׂא’ (to lift) or‘שׁאה’ (to crash into ruins). This research contends that ‘נשׂא’ is the correct lexical form of the Hebrew word ‘ותשא’ even suggesting that the author of the book of Nahum deliberately utilizes ‘‘נשׂא. This article employs textual criticism to prove this thesis.